1987
DOI: 10.1037/0012-1649.23.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Form and content in the development of deductive reasoning.

Abstract: Three experiments explored the development of formal logical reasoning between Grades 4 and 12 and the role of semantic content in the solution of Wason's (1966) selection task problems. In Experiment 1, subjects in the 8th, 10th, and 12th grades were tested on several familiar-content and several abstract-content selection problems. In Experiment 2, subjects in Grades 4, 8, and 12 were assessed on the familiar problems used in Experiment 1. In Experiment 3, subjects in Grades 4,6, and 8 were tested on novel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
72
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 8 publications
10
72
0
Order By: Relevance
“…In this task, individuals are given a conditional rule and are required to select conditions that would establish the validity or nonvalidity oftbe rule. The Overton et al (1987) experiments demonstrated that regardless of the specific nature of the content, a developmental progression occurs between 4th and 12th grades and deductive competence is largely unavailable before 8th grade. However, familiar semantic content also significantly enhanced performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this task, individuals are given a conditional rule and are required to select conditions that would establish the validity or nonvalidity oftbe rule. The Overton et al (1987) experiments demonstrated that regardless of the specific nature of the content, a developmental progression occurs between 4th and 12th grades and deductive competence is largely unavailable before 8th grade. However, familiar semantic content also significantly enhanced performance.…”
mentioning
confidence: 99%
“…Recently, Overton et al (1987) reexamined the role of semantic content in deductive reasoning in a series of developmental experiments that assessed performance on a modified version of the Wason selection task. In this task, individuals are given a conditional rule and are required to select conditions that would establish the validity or nonvalidity oftbe rule.…”
mentioning
confidence: 99%
“…Although most adolescents appear capable of Stage 3 understanding about the nature of logic, application of this competence to actual problems is imperfect and continues to develop at least through adolescence (O'Brien, 1987;Overton, 1990;Overton et al, 1987). Further reflection on the nature of logic may yield, in some highly educated adults, an increasingly explicit (Stage 4) metalogical understanding of the nature and interrelations of logical system and natural languages (Moshman, 1990a;Politzer, 1986).…”
Section: The Development Of Rationalitymentioning
confidence: 99%
“…By age 6 or 7 children typically have a fairly clear understanding of the various ways in which appearances can be deceiving and of the need to verify one's conceptions of reality by accumulating evidence, Elementary school-age children are still limited, however, in their level of understanding about the nature and justification of beliefs. Beginning about age 11, adolescents show an increasingly explicit understanding of the distinction between theories and data and the relation between these (Kuhn, 1989;Kuhn et al, 1988), and an increasing inclination to intentionally test theories by directly seeking potentially falsifying data (Moshman, 1979;O'Brien, 1987;O'Brien et al, 1986;O'Brien andOverton, 1980, 1982;Overton et al, 1987;Ward and Overton, 1990). Application of Stage 3 inductive rationality remains inconsistent even in adolescents and adults (Kuhn, 1989;Kuhn et al, 1988;Overton, 1990).…”
Section: Inductive Rationalitymentioning
confidence: 99%
“…Conclusion: Therefore, she will not be safer in a crash. (Invalid) As in class-inclusion syllogisms, the validity of the conclusion in conditional reasoning is based upon the information in the premises and the rules of logic.Many studies have documented the fact that conditional reasoning ability improves with age (e.g., Girotto, Gilly, Blaye, & Light, 1989;O'Brien & Overton, 1980;Overton, Ward, Noveck, Black, & O'Brien, 1987;Paris, 1973;Roberge, 1970;Rumain, Connell, & Braine, 1983;Sternberg, 1979;Wildman & Fletcher, 1977). Using a procedure similar to Roberge's (1970), Wildman and Fletcher (1977) asked 281 students, whose average ages were either 14, 16, 18 or 21 years of age, to judge the validity of several if-then syllogisms.…”
mentioning
confidence: 99%